2018
DOI: 10.1186/s12885-018-4718-6
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis of nucleophosmin overexpression in solid tumors: a meta-analysis

Abstract: BackgroundNucleophosmin is a non-ribosomal nucleolar phosphoprotein that is found primarily in the nucleolus region of cell nucleus, plays multiple important roles in tumor processes. Accumulated previous studies have reported a potential value of NPM acted as a biomarker for prognosis in various solid tumors, but the results were more inconsistency. We performed this meta-analysis to precisely evaluate the prognostic significance of NPM in solid tumors.MethodsClinical data were collected from a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(48 reference statements)
2
10
0
Order By: Relevance
“…In the proteomic study by Cruz et al [28], PEO1CarbR cells expressed more NPM1 than the parental PEO1 line, in line with the relative sensitivity to CX-5461, pointing to a protective role of the protein to the effects of this drug. Olausson et al [31] silenced NMP1 in human glioma cells which, when treated with the RNA polymerase I inhibitor Actinomycin D, sensitized cells to drug-induced apoptosis, in some agreement with our findings. This warrants further investigation of the sensitivity of cell lines with varying levels of NPM1 to the effects of CX-5461+/− radiation but this is beyond the scope of the current paper.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the proteomic study by Cruz et al [28], PEO1CarbR cells expressed more NPM1 than the parental PEO1 line, in line with the relative sensitivity to CX-5461, pointing to a protective role of the protein to the effects of this drug. Olausson et al [31] silenced NMP1 in human glioma cells which, when treated with the RNA polymerase I inhibitor Actinomycin D, sensitized cells to drug-induced apoptosis, in some agreement with our findings. This warrants further investigation of the sensitivity of cell lines with varying levels of NPM1 to the effects of CX-5461+/− radiation but this is beyond the scope of the current paper.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that NPM1 is overexpressed in drug-resistant ovarian cancer cells using an in-depth proteomic mass spectrometry study [28,29]. In addition, in high-grade ovarian serous cancer [30], a poorer patient outcome was associated with a significant overexpression of nuclear NPM1 and in transformed ovarian cancer cells [31], elevated levels of NPM1 were reported. Silencing of NPM1 expression by Kalra et al [31] led to aberrant double-strand break repair and p53/p21-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, NPM1 is overexpressed in a wide spectrum of solid human cancers including prostate [43], ovaries [44], nonsmall cell lung [45], liver [46], thyroid [47], colon [48], pancreas [49], as well as glioma [50], glioblastoma [51] and astrocytoma [52]. It has been highlighted that, in some cases, NPM1 increased expression correlates with the mitotic index and with the stage of tumor progression [1,53]. Even if the role of NPM1 overexpression in cancerogenesis is far to be fully understood, various scenarios have been proposed including the association of its overexpression with the upregulation of ribosome biogenesis and protein synthesis [54], but also with the stimulation of DNA repair following oncogene activation and with reduced apoptotic response [15,55].…”
Section: Role In Cancermentioning
confidence: 99%
“…This is in agreement with nucleolar activity being broadly upregulated in cancers ( Montanaro et al, 2008 ). Furthermore, other ribosome biogenesis factors, such as the Pol I transcription machinery and nucleophosmin, are also upregulated in cancer ( Bywater et al, 2013 ; Chen et al, 2018 ). We found concomitant upregulation of Treacle and UBF, nucleolin, and Pol I in lung and stomach cancer whereas a variable degree of overlap was observed in other cancer types.…”
Section: Discussionmentioning
confidence: 99%